Getting health reform right - Marc J. Roberts
This book provides a multi-disciplinary framework for developing and analysing health sector reforms, based on the authors' extensive international experience. It offers practical guidance, and stresses the need to take account of each country's economic, administrative, and political circumstances. The authors explain how to design effective government interventions in five areas - financing, payment, organization, regulation, and behaviour - to improve the performance and equity of health systems around the world